1984
DOI: 10.1002/hep.1840040311
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the Impaired Diuretic and Natriuretic Responses to a Sustained and Moderate Saline Infusion in Rats with Experimental Cirrhosis

Abstract: Kidney function and tubular handling of water and sodium by superficial nephrons, packed cell volume, total plasma proteins and albumin distribution space were studied in control and cirrhotic rats before and after a moderate and sustained saline infusion (3% body weight per 30 min + reposition of urinary losses). Tubular fluid samples were obtained from late proximal, early distal and late distal convolutions of superficial nephrons using micropuncture. Protein distribution was assessed by intravenous injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1986
1986
1990
1990

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In a model of cirrhosis in rats, which closely resembles the human disease in its histological (7) and functional aspects (8), we have demonstrated that cirrhotic animals are unable to excrete adequate amounts of urinary sodium after saline expansion (8,9). Recent data from our laboratory suggested that saline infusion is less effective in increasing intravascular volume in cirrhotic than in control rats, suggesting an inadequate natriuretic response to saline infusion (10).…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…In a model of cirrhosis in rats, which closely resembles the human disease in its histological (7) and functional aspects (8), we have demonstrated that cirrhotic animals are unable to excrete adequate amounts of urinary sodium after saline expansion (8,9). Recent data from our laboratory suggested that saline infusion is less effective in increasing intravascular volume in cirrhotic than in control rats, suggesting an inadequate natriuretic response to saline infusion (10).…”
mentioning
confidence: 74%
“…Recent data from our laboratory suggested that saline infusion is less effective in increasing intravascular volume in cirrhotic than in control rats, suggesting an inadequate natriuretic response to saline infusion (10).…”
mentioning
confidence: 98%
“…3). Several studies have demonstrated that increased sodium reabsorption occurs predominantly in the proximal renal tubule (Lopez-Novoa et al, 1984;Stein et af., 1974) and that circulating angiotensin I1 and catecholamines play an important role in regulating the percent contribution of the proximal tubule to the total renal sodium reabsorption (Cannon, 1977;Ichikawa et af., 1980Ichikawa et af., , 1984. Increased sodium reabsorption by the distal tubule and collecting duct at high aldosterone activity, also present under conditions of low cardiac index, is less relevant compared to angiotensin I1 avid proximal sodium reabsorption (Chonko et af., 1977).…”
Section: Discussionmentioning
confidence: 99%